Raise the Roof - Belga, Marie Edraline B. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment, 2023)
Significant change is observable within the landscape of Batad Rice Terraces, a UNESCO World Heritage site located in the Ifugao Province of the Philippines. One distinct fixture that is transforming within Batad’s landscape is the ‘bale’ or the traditional Ifugao house. The 'bale,' with its steep pyramidal thatched roof echoing the mountainous landform around it, is one of the most distinct features of Batad. The traditional use of the ‘bale' is, of course, as a residence. It also serves as a granary for harvested rice, with the topmost level considered sacred - allocated for rice, heirloom articles, and sculptures of the 'bulul' (rice guardians). Today, the bale(s) of Batad not only sit beside more modern-looking structures, but they themselves also have transformed uses and configurations. The study aimed to map, quantify, and characterize the transformations of Batad’s bale(s) through a multi-method combining drone photogrammetry, GIS-based geo-tagging, and actual field visits to document the bales’ conditions. Two maps pertaining to Batad’s bale(s) were produced from the study. First, a map showing the categorization of each bale based on their current occupancy type, i.e., residential, agricultural, tourism-related, etc. The second map shows a five-tier categorization based on the level of the bales’ physical transformations (or conservation) in terms of design and material. Supplementing these maps are photo-documentations of the bale(s), and anecdotal interviews with locals focusing on stories about the transformations of the traditional houses surveyed. All of these informed the narrative about the drivers of change and factors that support the sustainability of the bale(s) in Batad’s landscape.